The Effectiveness of Educational Intervention of Phonological Awareness on the Increase of Phonological Awareness among the Persian-Speaking Students with Cochlear Implant in First Grade of Primary Schools in Ahvaz City, Iran - Mohammad Reza Rostami; Nahid Baharloei (Vesnu Publications, 2018)
Introduction: Deaf children have lost part of their language learning course due to the lack of auditory input, and in most cases, they will face with many problems in their language-learning growth. One aspects of the language is phonological awareness that can be seen as an introduction to the development of future reading; moreover, training in phonological awareness is effective on development of decoding skills. The present study aimed to investigate the effectiveness of an educational intervention of phonological awareness, on the increase of phonological awareness among the Persian-speaking students with cochlear implant in first grade of primary schools in Ahvaz City, Iran. Materials and Methods: 28 Persian-speaking children with cochlear implant were randomly assigned to equal groups of experimental and control. The students' parents signed the formal consent form; then, the phonological awareness skill test was administered in both groups. The experimental group received the phonological awareness training, and the phonological awareness skill test was administered again in both groups. Results: After the intervention, the mean score of phonological awareness skill increased significantly in experimental group (P = 0.001). Moreover, the mean score of each phonological awareness subskill was significantly more increased in the experimental group compared to the control group (P < 0.050 for all). The intervention was most effective on segmentation skill, and least effective on awareness of the rhyme. Conclusion: The results of the study showed that the proposed phonological training program improved phonological awareness skills in children with cochlear implant. Application of this program is recommended.